Mycorrhiza governs plant-plant interactions through preferential allocation of shared nutritional resources: A triple (13C, 15N and 33P) labeling study - Faghihinia, Maede; Jansa, Jan (Frontiers in Plant Science, 2022)
Plant-plant interactions and coexistence can be directly mediated by symbiotic arbuscular mycorrhizal (AM) fungi through asymmetric resource exchange between the plant and fungal partners. However, little is known about the effects of AM fungal presence on resource allocation in mixed plant stands. Here, we examined how phosphorus (P), nitrogen (N) and carbon (C) resources were distributed between coexisting con- and heterospecific plant individuals in the presence or absence of AM fungus, using radio- and stable isotopes. Congeneric plant species, Panicum bisulcatum and P. maximum, inoculated or not with Rhizophagus irregularis, were grown in two different culture systems, mono- and mixed-species stands. Pots were subjected to different shading regimes to manipulate C sink-source strengths. In monocultures, P. maximum gained more mycorrhizal phosphorus uptake benefits than P.bisulcatum. However, in the mixed culture, the AM fungus appeared to preferentially transfer nutrients (33P and 15N) to P.bisulcatum compared to P. maximum. Further, we observed higher 13C allocation to mycorrhiza by P.bisulcatum in mixed- compared to the mono-systems, which likely contributed to improved competitiveness in the mixed cultures of P.bisulcatum vs. P. maximum regardless of the shading regime. Our results suggest that the presence of mycorrhiza influenced competitiveness of the two Panicum species in mixed stands in favor of those with high quality partner, P. bisulcatum, which provided more C to the mycorrhizal networks. However, in mono-species systems where the AM fungus had no partner choice, even the lower quality partner (i.e., P.maximum) could also have benefitted from the symbiosis. Future research should separate the various contributors (roots vs. common mycorrhizal network) and mechanisms of resource exchange in such a multifaceted interaction.